A status report on management of cleft lip and palate in India - A. Gopalakrishna; Karoon Agrawal (Indian Journal of Plastic Surgery)
Introduction: This national survey on the management of cleft lip and palate (CLP) in India is the first of its kind. Objective: To collect basic data on the management of patients with CLP in India for further evaluation. Materials and Methods: A proforma was designed and sent to all the surgeons treating CLP in India. It was publicized through internet, emails, post and through personal communication. Subjects: 293 cleft surgeons representing 112 centers responded to the questionnaire. Most of the forms were filled up by personal interview. Results: The cleft workload of the participating centers is between 10 and 2000 surgeries annually. These centers collectively perform 32,500–34,700 primary and secondary cleft surgeries every year. The responses were analyzed using Microsoft excel and 112 as the sample size. Most surgeons are repairing cleft lip between 3-6 months and cleft palate between 6 months to 1 year. Millard and Tennison repairs form the mainstay of lip repair. Multiple techniques are used for palate repair. Presurgical orthopedics, lip adhesion, nasendoscopy, speech therapy, video-fluoroscopy and orthognathic surgery were not always available and in some cases not availed of even when available. Conclusion: Management of CLP differs in India. Primary surgical practices are almost similar to other studies. There is a lack of interdisciplinary approach in majority of the centers, and hence, there is a need for better interaction amongst the specialists. A more comprehensive study with an improved questionnaire would be desirable.